„Regestrum Perceptorum et Expositorum Proventuum Venerabilis Capituli Cracoviensis” – księgi rachunkowe Kapituły Katedralnej w Krakowie z lat 1513-1812 (sygn. R.Cap.1-R.Cap.145) - Zych, Ewelina (Archiwa, Biblioteki i Muzea Kościelne, 2018)
The Archive of the Cracow Chapter contains a series of 160 account books (from the first half of the 16th century to the beginning of the 20th century). The fi rst 145 books refer to modern times. A dozen or so books concern the 19th and early 20th centuries, and the oldest book dates back to 1513. These account books were produced by the procurators of the Chapter, later – offi cials subordinate to them. The books contain information on the expenses related to the property of the Chapter (houses, villages, manors, landed property), individual canons, liturgy celebrated in the Cathedral (both daily and such celebrations as funerals of bishops or royal coronations), remuneration for people working for the Chapter (e.g. notaries, procuratores, rectors of the cathedral school). In addition, any renovations, changes in the equipment of the cathedral and the chapter buildings were carefully recorded in them. Due to the amount and variety of information, the account books are a mine of knowledge for historians, art historians and conservators; however, these books have sporadically been used by researchers so far. There are many similarities in the account books that make up the series, which is why the same form was used for their description; it was only slightly modifi ed over the decades. In the collection marked with the reference number R.Cap., there are other account books concerning only some of the Chapter activities such as expenses for the cathedral sacristy, the sums stored in the treasury and rough drafts.